European real estate prices: Collection and processing of sale and rental prices in 18 European countries - Michael Koetter; Felix Noth (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2022)
Real estate markets are pivotal to financial stability given their dual role as the underlying asset of crucial financial products in financial systems, such as mortgage loans and asset-backed securities, and the primary source of household wealth alike. As such, they also play traditionally a crucial role for the transmission of monetary policy. Imbalances and sudden corrections in real estate markets have been the root cause of many financial crises over the last decades. But whereas some national, often survey-based indicators of real estate prices are provided by central banks and statistical offices, a comprehensive collection of purchase prices, rents, and proxies for the liquidity of European real estate markets is lacking. The IWH European Real Estate Index (EREI) seeks to fill this void for residential property. This technical report describes the gathering and processing of sale and rental prices for properties in 18 European countries. We provide the general scrapeing step in the section before describing country-specific details for each country in separated sub-sections.
Keywords: 330; Immobilienmarkt; Immobilienpreise; Wohnimmobilien; IWH-EREI